PERBANDINGAN HUKUM NEGARA INDONESIA DAN NEGARA INGGRIS MENGENAI PERKOSAAN DI BAWAH UMUR - Khrisdianto Risyad; Vientje Ratna Multiwijaya (Reformasi Hukum Trisakti, 2022)
Given that children will be the nation's future leaders and heirs, child protection is implemented with this understanding in mind. The prevalence of sexual predators is rising, starting with the lower middle class and moving up to the upper middle class. Law Number 35 of 2014 gives Indonesia the tools to protect children, but is this sufficient? The UK has general provisions in the Penal Code up to provisions in The Sexual Offenses Act 2003 for the protection of children with sexually vulnerable characteristics. Problem formulation; comparing and contrasting the components of underage rape using research techniques from literature research; the type of study employed is normative juridical; with the nature of the research, which involves applying deductive reasoning to generate conclusions from descriptive analytical, primary data, and qualitative data analysis methodologies. In terms of the research's findings, analysis, and conclusion, there are four areas of similarity and ten points of difference, one of which is the absence of a law on sexual violence in Indonesia, which would serve as a vehicle for the nation's future generations' protection.